2015
DOI: 10.1089/apc.2015.0100
|View full text |Cite|
|
Sign up to set email alerts
|

“Just Because It's Out There, People Aren't Going to Use It.” HIV Self-Testing Among Young, Black MSM, and Transgender Women

Abstract: HIV disproportionately affects young black MSM and transgender women in the US. Increasing HIV testing rates among these populations is a critical public health goal. Although HIV self-tests are commercially available, there is a need to better understand access to and uptake of HIV self-testing among this population. Here, we report results of a qualitative study of 30 young black MSM and transgender women residing in the New York City area to understand facilitators of and barriers to a range of HIV testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 47 publications
8
63
0
Order By: Relevance
“…These consequences included fears of marital disruption and suicidal ideation [17] due to the absence of pre- or post-test counseling. Similar fears have been documented in other studies [18,19] especially with regard to fears of what could happen in the home in the event that one of the partners is HIV-positive, in the absence of post-test counseling. To deal with these fears, we provided adequate preparation to improve the women’s technical competencies and negotiation efficacy to improve their ability to deliver the kits as well as encourage their partners to test alone or together with them.…”
Section: Discussionsupporting
confidence: 84%
“…These consequences included fears of marital disruption and suicidal ideation [17] due to the absence of pre- or post-test counseling. Similar fears have been documented in other studies [18,19] especially with regard to fears of what could happen in the home in the event that one of the partners is HIV-positive, in the absence of post-test counseling. To deal with these fears, we provided adequate preparation to improve the women’s technical competencies and negotiation efficacy to improve their ability to deliver the kits as well as encourage their partners to test alone or together with them.…”
Section: Discussionsupporting
confidence: 84%
“…1921 Moreover, at-home testing is acceptable among internet-using MSM: a study of 6,163 MSM recruited online found that 62% of participants reported being very likely and 20% likely to accept a free anonymous at-home HIV test as part of future online prevention studies. 12 …”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that HIV diagnoses made in non-clinical settings, such as mobile vans or peer networks, are less effective in linking newly-identified cases to HIV care and treatment [51]. In our study, a misperceived advantage of HIVST among a few men was the omitted need for follow-up clinical visits.…”
Section: Discussionmentioning
confidence: 61%
“…From a consumer perspective, kit pricing is a reasonable concern. Previous research has shown that the unit cost of an HIVST kit accounts for half of the total costs of HIVST for consumers [28] and that kit price is a barrier to HIVST acceptability [51]. Despite the appeal of HIVST in reducing costs related to clinic travel and waiting time, addressing cost concerns of the price of HIVST by providing free or subsidized HIVST kits may be necessary to fully reduce testing barriers in low-income men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation